Efektivitas pemberian zinc pada anak dengan pneumonia: A systematic review - Muhammad Fikri Nasrun; Edward Pandu Wiriansya; Bulkis Natsir; Muh Alfian Jafar; Nur Aisyah (Holistik Jurnal Kesehatan, 2026)
Background: Acute respiratory tract infections, particularly severe pneumonia are a leading cause of death in children under five, particularly in developing countries like Indonesia. Zinc is an essential micronutrient that plays a crucial role in maintaining immune function and aiding the healing process of infections. However, the effectiveness of zinc supplementation in severe pneumonia remains controversial due to varying research results. Purpose: To examine the effectiveness of zinc administration as an adjuvant therapy in severe pneumonia through a systematic review. Methods: Literature search in electronic databases such as PubMed, Scopus, Sinta, and Google Scholar from 2020-2025. Studies that met the inclusion criteria were analyzed to evaluate the impact of zinc supplementation on the duration of hospitalization, symptom recovery, and safety of its use in severe pneumonia. Result: That zinc supplementation effectively accelerated recovery by reducing the duration of fever, shortness of breath, and length of hospital stay, especially in children aged 2 to 60 months. Zinc also plays a role in enhancing the immune response and reducing airway inflammation. Zinc use is recommended in areas with a high prevalence of zinc deficiency and a high risk of severe pneumonia. Conclusion: Zinc supplementation is a promising adjunctive therapy in the management of severe childhood pneumonia. However, further research is needed to determine the optimal dose, duration of therapy, and effectiveness in a broader age group and clinical setting for appropriate integration into clinical practice.   Keywords: Acute Respiratory Tract Infections (ARI); Children; Pneumonia; Zinc.   Pendahuluan: Infeksi Saluran Pernapasan Akut (ISPA), khususnya pneumonia berat merupakan penyebab utama kematian pada anak di bawah lima tahun, terutama di negara berkembang seperti Indonesia. Zinc adalah mikronutrien esensial yang berperan penting dalam menjaga fungsi imun dan membantu proses penyembuhan infeksi. Namun, efektivitas suplementasi zinc pada pneumonia berat masih menjadi perdebatan akibat hasil penelitian yang bervariasi. Tujuan: Untuk menelaah efektivitas pemberian zinc sebagai terapi adjuvan pada pneumonia berat melalui pendekatan systematic review. Metode: Penelitian literatur melalui basis data elektronik seperti PubMed, Scopus, Sinta, dan Google Scholar dari tahun 2020-2025. Studi yang memenuhi kriteria inklusi dianalisis untuk mengevaluasi dampak suplementasi zinc terhadap durasi rawat inap, pemulihan gejala, serta keamanan penggunaannya pada pneumonia berat. Hasil: Suplementasi zinc efektif mempercepat pemulihan dengan mengurangi durasi demam, sesak napas, dan lama perawatan di rumah sakit, terutama pada anak usia 2-60 bulan. Zinc juga berperan dalam meningkatkan respons imun dan menurunkan peradangan saluran pernapasan. Penggunaannya lebih disarankan pada daerah dengan prevalensi defisiensi zinc tinggi dan risiko pneumonia berat. Simpulan: Suplementasi zinc merupakan terapi tambahan yang menjanjikan dalam manajemen pneumonia berat anak. Namun, diperlukan penelitian lebih lanjut untuk menentukan dosis optimal, durasi terapi, serta efektivitas pada populasi usia dan kondisi klinis yang lebih luas guna integrasi yang tepat dalam praktik klinis.   Kata Kunci: Anak; Infeksi Saluran Pernafasan Akut (ISPA); Pneumonia; Zinc.